Evaluation of Potential Hepatotoxicity Induced by Bortezomib - Mutluay, Duygu; Abou Monsef, Yanad; Yücel Tenekeci, Gözde (Acta Scientiae Veterinariae, 2021)
Background: Bortezomib, an inhibitor of 26S proteasome, is an anti-cancer therapeutic agent used in different cancer types. It leads to the arrest of the cancerous cell cycle by inhibiting angiogenesis and inducing apoptosis. Liver is the vital organ for detoxification and excretion of toxic products. The treatment with chemotherapy is a challenge, drugs are used to destroy cancer cells, but healthy cells can be affected during cancer treatment as well. The main objective of this study was to analyze the histopathological and biochemical effects of bortezomib on liver. Materials, Methods & Results: Twenty-four female C57BL/6 mice were distributed into 4 groups, bortezomib injected treatment groups (Btz1, Btz2) and saline injected control groups (C1, C2). Bortezomib and saline treated twice per week for 6 weeks and sacrificed at the end of one day (Btz1, C1) and 4 weeks (Btz2, C2) after the last injection. Liver samples were examined for histopathological analysis and the serum samples processed for biochemical analysis. Tissue samples were fixed, routinely processed, sectioned, and stained with Hematoxylin and Eosin (H&E). Periodic Acid-Schiff (PAS), Sudan Black staining and Masson’s trichrome histochemical staining methods were performed to characterize the lesions. Histopathological analysis of the Btz1 and Btz2 groups revealed acute hepatic morphological changes such as hepatocellular swelling (cloudy swelling), necro-inflammatory reaction, and increased mononuclear polyploidy. Based on the negative staining with PAS and Sudan Black staining, hepatocellular swelling was diagnosed as hydropic degeneration. Necro-inflammatory reaction observed in the form of acute hepatitis was composed of mainly mononuclear cell infiltration accompanied by multifocal necrotic foci. Kupffer cell proliferation was observed in parallel with degenerative and necrotic changes. An Increase in hepatocellular mononuclear polyploidy visualized as hepatocytes with a single enlarged nucleus was detected in all liver sections of Btz1 and Btz2 groups Individual cases of cholestasis (n = 1) and mild hepatic fibrosis (n = 1) were also reported. Significant elevated levels of alanine aminotransferase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP) and gamma-glutamyl transferase (GGT) were detected in bortezomib treated groups. Discussion: Few clinical casesreported liver injury related to bortezomib used for cancer treatment. However, the liver was not considered as a target for bortezomib treatment. Our data suggesting that bortezomib caused liver damage and induce elevations in serum levels. The reported hepatic lesions including hepatocellular swelling, acute hepatitis and mononuclear polyploidy were mainly mild and moderate in severity. The increase of polyploidy in liver tissue of mice treated with bortezomib in this study was explained as a reaction of the liver facing the drug-induced hepatic damage. The mechanism leading to the hepatotoxicity of bortezomib treatment is not known but the production of a toxic metabolite through its metabolism in the liver can be suggested. Moreover, no recovery was also observed in histopathological and biochemical analyses suggesting that the bortezomib effect is non-reversible four weeks after the drug was withdrawn. Patients should be informed about the possibility of acute drug-induced hepatitis and hepatotoxicity of this chemotherapeutic agent after the treatment. Keywords: bortezomib, cancer, chemotherapy, hepatotoxicity, liver, proteasome inhibitor.